MORC Proteins: Novel Players in Plant and Animal Health - Koch, Aline; Kang, Hong-Gu; Steinbrenner, Jens; Dempsey, D'Maris A.; Klessig, Daniel F.; Kogel, Karl-Heinz (Frontiers in Plant Science, 2017)
Microrchidia (MORC) proteins comprise a family of proteins that have been identified in prokaryotes and eukaryotes. They are defined by two hallmark domains: a GHKL-type ATPase and an S5 fold. MORC proteins in plants were first discovered via a genetic screen for Arabidopsis mutants compromised for resistance to a viral pathogen. Subsequent studies expanded their role in plant immunity and revealed their involvement in gene silencing and transposable element repression. Emerging data suggest that MORC proteins also participate in pathogen-induced chromatin remodeling and epigenetic gene regulation. In addition, biochemical analyses recently demonstrated that plant MORCs have topoisomerase II (topo II)-like DNA modifying activities that may be important for their function. Interestingly, animal MORC proteins exhibit many parallels with their plant counterparts, as they have been implicated in disease development and gene silencing. In addition, human MORCs, like plant MORCs, bind salicylic acid and this inhibits some of their topo II-like activities. In this review, we will focus primarily on plant MORCs, although relevant comparisons with animal MORCs will be provided.